A wind-induced negative damping method to achieve high-energy orbit of a nonlinear vibration energy harvester. (21st January 2021) - Lan, Chunbo; Hu, Guobiao; Liao, Yabin; Qin, Weiyang
Abstract: Maintaining high-energy orbit oscillation of a nonlinear vibration energy harvester (VEH) is the key to achieve high-performance, broadband energy harvesting. Conventional orbit-jump strategies, such as mechanical modulation or electrical control methods, need to consume the limited harvested energy and may unfavourably reduce the energy harvesting efficiency. To avoid the undesired energy consumption, we focus on utilizing the overlooked wind energy to assist a nonlinear VEH to attain the preferred high-energy orbit. The novel orbit-jump method proposed in this letter is based on the wind-induced negative damping mechanism and the resultant self-excited behaviour. Both numerical simulation and experimental results validate the feasibility of the proposed method to efficiently trigger the high-energy orbit oscillations of a nonlinear VEH. Moreover, the required wind energy to achieve self-excited oscillation for different excitation frequencies and acceleration levels, is quite stable and can be easily satisfied, which demonstrates good robustness for practical applications.